The Eastern and Western mystic philosophy and allness reflected in Andrei Tarkovsky’s films - Sosnin, Alexey; Balakina, Julia; Belova, Polina (Slavia Centralis, 2021)
The research cited in the article aims to compare the educational language policy officially pursued in the Republic of Crimea with the de facto language policy as it is reflected in the media discourse and social networks over the period 2014-2020. Methodologically, the research draws upon the theory of constructing social issues (Spector, Kitsuse 1977), which is based on the principles of social constructivism (Berger, Luckmann 1966). The study employs qualitative content analysis as the basic working procedure. The authors conclude that the official data on vernacular education in the Crimea partially coincide with the information published in the media and discussed in social networks. This particularly concerns the diminishing rate of those getting education in the Ukrainian language. Overall, the educational language policy pursued in the region enjoys popular support with the majority of the Crimeans (who are speakers of Russian).